2022
DOI: 10.1007/s12559-022-10041-3
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation to Identify Optimal Setup for Automated Assessment of Dysarthric Intelligibility using Deep Learning Technologies

Abstract: Recent advances in deep learning have provided an opportunity to improve and automate dysarthria intelligibility assessment, offering a cost-effective, accessible, and less subjective way to assess dysarthric speakers. However, reviewing previous literature in the area determines that the generalization of results on new dysarthric patients was not measured properly or incomplete among the previous studies that yielded very high accuracies due to the gaps in the adopted evaluation methodologies. This is of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…For alleviating the above-mentioned limitations, a number of supportive systems to assess dysarthria via patient's speech or vocalperformance analysis have been proposed in literature. Examples include [12,25,26] which investigate the feasibility of machine learning (ML) methods for the analysis of audio-data collected in hospital and home scenarios. In [27,28], a telemonitoring-based application is introduced to automatically assess the evolution in the intelligibility of the speech of dysarthric patients.…”
Section: Dysarthria Assessmentmentioning
confidence: 99%
“…For alleviating the above-mentioned limitations, a number of supportive systems to assess dysarthria via patient's speech or vocalperformance analysis have been proposed in literature. Examples include [12,25,26] which investigate the feasibility of machine learning (ML) methods for the analysis of audio-data collected in hospital and home scenarios. In [27,28], a telemonitoring-based application is introduced to automatically assess the evolution in the intelligibility of the speech of dysarthric patients.…”
Section: Dysarthria Assessmentmentioning
confidence: 99%
“…In the best situation, the proposed system gave an accuracy of 93.97% under the speaker-dependent scenario and 49.22% under the speaker independent scenario for the UA-Speech database. Hall et al in [22] reported the optimal setup of deep learning-based dysarthric intelligibility assessment and explained different evaluation strategies.…”
Section: Related Workmentioning
confidence: 99%
“…• As a recent technical development, the application of machine learning technology in dysarthria research has increased enormously, with a growth of about 900% since the beginning of this century. However, despite the great promise of this powerful technology, reports on standard applications in clinical care are still lacking and approaches based on methodologically rigorous models still yield disappointing results [14,15]. Among the major obstacles that need to be overcome is the problem of how we can collect training datasets that guarantee accurate and unbiased predictions, particularly considering the large variability that exists across dysarthria types, disease stages, degrees of severity, and individual idiosyncrasies; not to mention the variability as a function of age and gender, dialectal variants, ethnicities, mood, motivation, or factors related to the quality of acoustic data.…”
mentioning
confidence: 99%